Remnant cholesterol: an independent, dose-dependent risk factor for hyperuricemia in a normolipidemic chinese population - Xiong, Huali; Ma, Fengxun (Frontiers in Endocrinology, 2026)
BackgroudThe association between remnant cholesterol (RC) and hyperuricemia (HUA) remains unclear in the general population with entirely normal lipid profiles and no prior lipid-lowering therapy. This study aimed to investigate the association between RC and HUA in a normolipidemic Chinese population.MethodWe recruited 2,171 participants aged 30–79 years from Rongchang, Chongqing Municipality, southwest China, as part of the China Multi-Ethnic Cohort Study. Logistic regression, restricted cubic spline (RCS), and mediation analyses were applied to evaluate the association between RC and HUA. Furthermore, subgroup and sensitivity analyses were conducted to assess the consistency of the findings.ResultsA total of 2,171 participants were enrolled, with a mean (SD) age of 50.43 (12.21) years. The overall prevalence of HUA was 9.07%, and the prevalence across RC quartiles (Q1: 0.14–0.43, Q2: 0.44–0.60, Q3: 0.61–0.89, and Q4: ≥0.90 mmol/L) were increased stepwise: 4.45%, 8.32%, 12.88%, and 19.08%, respectively(Pfor trend < 0.001). Logistic regression revealed that the ORs were 1.753 (95%CI: 1.093–2.809), 2.900 (95%CI: 1.845–4.558), and 4.268 (95%CI: 2.373–7.674) in Q2, Q3, Q4, respectively, compared to Q1 after adjusting for confounding factors. RCS revealed that RC was positively associated with HUA by a linear model (Pfor overall < 0.001, Pfor nonlinear>0.05), with no evidence of a threshold. These findings remained robust in sensitivity analyses that excluded participants with hypertension, diabetes, overweight/obesity or central obesity. Subgroup analyses revealed consistent RC-HUA associations across strata of age, sex, smoking status, drinking status, hypertension status, diabetes status, overweight/obesity status, central obesity status, DASH score. Mediation analyses revealed a potential mediation effect between RC and uric acid(UA), indicating that IR may mediated 39.91% of the total association between RC and UA.ConclusionRemnant cholesterol emerges as a fully independent, dose-dependent, and readily modifiable determinant of incident hyperuricemia in Chinese adults, which can serve as an ideal candidate for inclusion in routine metabolic panels and presenting as a hypothesis for future longitudinal research.